2014
DOI: 10.1111/acem.12503
|View full text |Cite
|
Sign up to set email alerts
|

Improving Attendance at Post–Emergency Department Follow‐up Via Automated Text Message Appointment Reminders: A Randomized Controlled Trial

Abstract: Objectives: Patients discharged from the emergency department (ED) are often referred for primary care, specialty, or other disease-specific follow-up appointments. Attendance at these scheduled followup appointments has been found to improve patient outcomes, decrease ED bounce-backs, and reduce malpractice risk. Reasons for missing follow-up visits are complex, but the most commonly reason cited by patients is simply forgetting. In this study the authors evaluated the ability of an automated text message rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
91
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 25 publications
0
91
0
Order By: Relevance
“…Effective, outcomes, and communicative were mentioned in 6/60 occurrences (10%). 27,28,30,[37][38][39][40]45,46,48,53,[54][55][56]58 mHealth can change behaviour through feedback. It can mentally stimulate patients to delay the advance of dementia, improve triage decisions and arrangement of transportation through communication channels, increase self-efficacy augmenting existing interventions and thereby outcomes.…”
Section: Facilitatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective, outcomes, and communicative were mentioned in 6/60 occurrences (10%). 27,28,30,[37][38][39][40]45,46,48,53,[54][55][56]58 mHealth can change behaviour through feedback. It can mentally stimulate patients to delay the advance of dementia, improve triage decisions and arrangement of transportation through communication channels, increase self-efficacy augmenting existing interventions and thereby outcomes.…”
Section: Facilitatorsmentioning
confidence: 99%
“…The outcomes theme included early diagnosis, mobile interventions to stimulate mental activity, encouraging a more active role of patients in their conditions, and increased medication and therapy adherence, and an enabler to detect falls. 27,39,45,46,56,58 Mobile technology can also serve as a tool of communication to augment existing modalities to provide real-time data and increase the level of communication between patient and provider. 28,30,37,40,45,54 Quality of life was mentioned in 5/60 occurrences (8%), and it encompassed observations that mobile technology can make life easier, convenient and more comfortable for the user.…”
Section: Facilitatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arora et al 11 performed an RCT of ED patients with an outpatient follow-up scheduled at the time of an ED discharge. Patients who received an automated text message reminder were more likely to attend their scheduled follow-up visit (72.6% in the intervention group compared with 62.1% in the control group; Δ 10.5%; 95% CI: 0.3%, 20.8%; number needed to treat 9.5).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who received an automated text message reminder were more likely to attend their scheduled follow-up visit (72.6% in the intervention group compared with 62.1% in the control group; Δ 10.5%; 95% CI: 0.3%, 20.8%; number needed to treat 9.5). 11 Wolff et al 12 conducted an RCT of adolescent females diagnosed with pelvic inflammatory disease, which found that patients who received standard discharge instructions plus text message reminders were more likely to receive recommended follow-up care within 72 hours of the ED discharge compared to patients who received standard discharge instructions (relative risk 2.9, 95% CI: 1.4, 5.7; number needed to treat 4, 95% CI: 1.4, 5.7). 12 These ED-specific findings are consistent with previous studies demonstrating improved follow-up adherence in other health care settings when text messaging was used.…”
Section: Discussionmentioning
confidence: 99%